Flexural strength and viscosity of dental luting composite reinforced with zirconia and alumina (Bangladesh Journal of Medical Science, 2024)
Objectives Optimum flexural strength and viscosity are essential for longevity while efficiently handling dental luting composite. This study aims to investigate the effects of zirconia and alumina on the flexural strength (FS)and viscosity of dental cement made of silica rice husk. Materials and Methods Study groups with different percentages of weight (wt.): Group 1 (3 wt.% zirconia), Group 2 (3 wt.% alumina), and Group 3 (3 wt.% zirconia and 2 wt.% alumina), negative control specimen (0 wt.% zirconia/ alumina) and Rely-X U200 (3M ESPE). A universal testing machine and a rheometer were used to test FS and viscosity, respectively. One-way ANOVA and post-hoc Bonferonni test were used for data analyses. Results and Discussion FS and viscosity for Group 3 (3 wt.% zirconia and 2 wt.% alumina) were significantly higher compared to the negative control (p